2022
DOI: 10.1111/1346-8138.16583
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of patients with pustular psoriasis in the Japanese Society for Psoriasis Research from 2017 to 2020

Abstract: Psoriasis is a common chronic inflammatory skin disease that can present at any age. 1 Various risk factors and comorbidities are known to interact with each other and elicit disease. 2 The Japanese Society for Psoriasis Research (JSPR) has been conducting annual epidemiological surveys of patients with psoriasis since 1982. [3][4][5][6] reported 28 628 cases that were enrolled

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…reported stress, infection and certain drugs as the most common triggers for exacerbations of pustular psoriasis in patients in Japan. 31 GPP flares also occur without a known trigger. Idiopathic flares have been reported in 15% of patients by Choon et al and 57% of patients by Zheng et al 5,29 Even when initial flares have known triggers, subsequent flares can occur without known causes.…”
Section: G Pp Patient Burdenmentioning
confidence: 99%
See 1 more Smart Citation
“…reported stress, infection and certain drugs as the most common triggers for exacerbations of pustular psoriasis in patients in Japan. 31 GPP flares also occur without a known trigger. Idiopathic flares have been reported in 15% of patients by Choon et al and 57% of patients by Zheng et al 5,29 Even when initial flares have known triggers, subsequent flares can occur without known causes.…”
Section: G Pp Patient Burdenmentioning
confidence: 99%
“…The same study reported 58.4% of patients received oral medication, 44.0% received biologics and 9.6% received phototherapy. 31 In another retrospective analysis of hospitals in Japan, 1516 patients with GPP were identified that were treated with biologics (19%), oral agents (63%) and corticosteroids only (18%). 16 Patients with GPP treated with biologics had significantly less in-hospital morbidity (5.4% biologics vs. 8.2% oral agents vs. 12% corticosteroids only, p = 0.02), respiratory complications (1.7% vs. 3.7% vs. 8.8%, p < 0.001), and mortality (1.0% vs. 3.7% vs. 9.1%, p < 0.001).…”
Section: Treatment Utilizationmentioning
confidence: 99%
“…It accounts for only 0.6%-13.1% of all childhood psoriasis. [1][2][3] The loss-of-function mutation of interleukin-36 receptor antagonist (IL36Ra) has been associated with development of GPP. 4 Interestingly, IL-17 mRNA levels were also noted to be higher in pustular psoriasis in comparison with other clinical subtypes.…”
Section: E T T E R T O T H E E D I T O R Infantile Generalized Pustul...mentioning
confidence: 99%
“…A range of factors have been identified as triggers of GPP, including pregnancy, infections, and starting or withdrawing treatments such as systemic corticosteroids or anti‐psoriatic therapy 2,6,7,9,10 . Additionally, psoriasis vulgaris (PsV) may precede GPP, with 34%–65% of patients with GPP having prior or concomitant PsV 2,6,9–11 ; it was recently shown that, in Japan, 29.7% of patients with GPP have prior or concomitant PsV 12 . PsV is a papulosquamous skin disease characterized by acanthosis, parakeratosis, and dermal inflammatory infiltrates 2,13 .…”
Section: Introductionmentioning
confidence: 99%
“…2,6,7,9,10 Additionally, psoriasis vulgaris (PsV) may precede GPP, with 34%-65% of patients with GPP having prior or concomitant PsV 2,6,[9][10][11] ; it was recently shown that, in Japan, 29.7% of patients with GPP have prior or concomitant PsV. 12 PsV is a papulosquamous skin disease characterized by acanthosis, parakeratosis, and dermal inflammatory infiltrates. 2,13 PsV can present with a few scattered red, scaly plaques or can involve a greater body surface area.…”
mentioning
confidence: 99%